Discourse conditions in language change: from binominal to aspectualizer be in the middle or midst of V-ing. (January 2016) - Van Rompaey, Tinne
Abstract: This article examines the role of discourse relations in the emergence of English semi-auxiliaries of the type be in the NP1 of NP2 / V -ing expressing progressivity, for example in I was in the middle of washing my hair . On the basis of Old, Middle and Modern English corpus data, I will (i) reconstruct the path of change from partitive binominal construction over complex preposition in the middle/midst of NP2 to progressive semi-auxiliary and (ii) explore how step-by-step changes in the discourse-functional features of the NP2s shape this development. More specifically, I will show that event NP2s in the intermediate complex preposition and nominal aspectualizer stages offer the pragmatic choice of encapsulating or summarizing the information previously mentioned in a compact way and that this discourse-functional flexibility of the binominal source constructions proves to be a prerequisite for the emergence of the aspectual semi-auxiliary. On the basis of this case study, I will argue that discourse-functional factors have to be taken into account to adequately explain the processes of change originating in binominal source constructions, even if the output or target construction of the development is in itself not a discourse-organizing marker, as is the case in the history of the progressive aspectualizer be in the middle/midst of V -ing. Highlights: Progressive be in the middle/midst of developed from a binominal construction. Discourse-functional changes are a prerequisite for its emergence. Textual factors play a role in the development of non-discourse-organizing markers. Binominal constructions are prone to change because of their discourse flexibility.